Progression dynamics of Zika fever outbreak in El Salvador during 2015–2016: a mathematical modeling approach. (May 2017) - Kumar, Narender; Abdullah, Mohd; Faizan, Md Imam; Ahmed, Anwar; Alsenaidy, Hytham A; Dohare, Ravins; Parveen, Shama
Aim: The aim of the study was to utilize mathematical modeling to investigate effect of different parameters that affected mosquito-borne transmission of Zika virus during 2015–2016 outbreak in El Salvador. The model can be used to predict outbreaks at various geographical regions utilizing different conditions.Materials & methods: A susceptible-exposed-infectious-recovered mathematical model was generated for disease progression.Results: The model correlated with actual number of reported cases and stability analysis. The value of reproduction number ( Ro = 4.5537) indicated rapid spread of viral infection suggestive of an outbreak. Simulations revealed that transitional parameters affected disease progression.Conclusion: Investigation of progression of infection in a given population using mathematical models may assist in prediction of outbreaks and in formulation of control measures.